Guidelines for Enhancing Skills and Resources for Participation and Sustainability - Hoadley, Marie; Limpitlaw, Daniel; Sheehey, Bren (World Bank, Washington, DC, 2014)
The Guidelines provided here are designed to encourage the development of the skills and resources needed by the community and the mining operation in a participatory and consultative way. This process should commence at exploration stage and continue through to closure. If this is done, each preceding stage will build on the next so that, at closure, the community has the skills and capacity to continue to develop without the mine. The audience for the recommendations in these Guidelines is community development personnel at mining operations, local government representatives, and the staff of different organizations and networks that constitute a community. The recommendations make suggestions around the practical aspects of community consultation and participation.